Attitude of Sultan Kudarat State University Laboratory High School Students and Teachers on Proposed “No Homework Policy” Bill - Jenevieve Lumbu-ani; Hasan P. Abusama; Jasmine L. Pangarungan; Jheanese Joy L. Danozo; Marielle Joy L. Estrada; Hasandra A. Hasan; Luis Henri A. Moscoso (Indonesian Journal of Educational Research and Technology, 2021)
The purpose of our study is to understand the attitude of the university students and teachers on the proposed ‘No Homework Policy” bill and how it could impact their studies and personal lives. The main objective was focused on (1) understanding the impact of the “No Homework Policy” bill to the students and teachers if the said policy bill will be implemented, (2) knowing the struggles of the students and teachers when it comes to homework, and (3) finding out the possible solution that could be implemented to lessen the struggles of both students and teachers regarding homework. A phenomenological design was used as an approach to conduct this study. Based on the results, most of the students are in favor of the said proposed bill. However, some teachers are against or undecided about it. The results also showed that the said proposed bill could affect both students and teachers in a positive and also a negative way. This study does not only help the student to realize how homework can impact their academic performances but also support the teacher to improve the capacity of their teaching skills and be aware of the struggles of the students with regards to homework